Collaborative visit from Bali Tourism Polytechnic, Indonesia to Universiti Teknologi MARA for QS Ranking insights and best practices / Noorsuhada Md Nor … [et al.] - Md Nor, Noorsuhada; Ariffin, Hashim Fadzil; Ngelambong, Anderson; Othman, Nor Azlan; Mohd Azhari, Nor Khadijah; Damanhuri, Nor Salwa (UiTM Global @ Office of International Affairs, 2024)
From 2–3 November 2023, Universiti Teknologi MARA (UiTM) Pulau Pinang Branch, Malaysia, hosted a delegation from Bali Tourism Polytechnic (BiTP), Indonesia, for a courtesy visit and benchmarking session. The focus of the session was to enhance institutional strategies, particularly in relation to the prestigious QS World University Rankings. This visit highlighted UiTM’s dedication to strengthening its international partnerships and improving global competitiveness.